Table of contents, editorial board, and other front matter - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1978)
Editorial front matter and table of contents for vol.61, no.3, Oct.-Nov. (1978) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education.